Systematic Review: Protective Factors from the Risks of Stunting in Breastfeeding Period - Riris Diana Rachmayanti; Zulfa Kevaladandra; Faisal Ibnu; Nur Khamidah (Jurnal Promosi Kesehatan Indonesia, 2022)
Background: Stunting is a chronic nutrition condition marked by improper growth of body height compared to one’s age. One of the factors that affect stunting is exclusive breastfeeding as breast milk contains macronutrients, micronutrients, and bioactive substances to support the growth and development of children under five and act as an anti-infection. Non-optimal breastfeeding causes children to have inadequate nutrition intake and body immunity, which may result in malnutrition and stunting. This study aims to identify the effects of exclusive breastfeeding on the incidence of stunting in children under five.Method: A systematic review was conducted using eight indexed articles with keywords of "Stunting", "ASI Eksklusif" (t/n: Exclusive Breastfeeding), "Gizi Ibu dan Anak (t/n: Nutrition of Mothers and Children)", "Stunting pada Balita (t/n: Stunting in Children Under 5)", "Exclusive Breastfeeding", "Nutritional Status and Exclusive Breastfeeding", and PICOT. Articles published within the last seven years (2014-2020) were selected. The articles should address health education to mothers with children aged < 5 years old without a control group, and should show a relation between exclusive breastfeeding and the incidence of stunting. Besides, they should be analytical and observational research written in English and Indonesian.  Results: Eight articles selected overall showed that exclusive breastfeeding was significantly related to the incidence of stunting in children under five. Exclusive breastfeeding is protection against stunting as breast milk contains nutritions that can increase body immunity, prevent infection, and nutritional substances for optimal growth and protection from the risks of chronic diseases. Exclusive breastfeeding is one of the significant factors that affects stunting in children under five.